LEVERAGE AND LIQUIDITY LEVELS: THE IMPACT ON FINANCIAL DISTRESS IN VARIOUS SECTORS OF VARIOUS INDUSTRIES - Putri, Diana Rizki Cahyani; Andayani, Sari (International Journal of Economy, Education and Entrepreneurship (IJE3), 2024)
This study is useful to determine the effect of leverage and liquidity on financial distress in various industrial sectors. The population used in this study is companies in various industrial sectors listed on the Indonesia Stock Exchange (IDX) during 2019 to 2022, which was obtained by 56 companies. The sample collection technique used is purposive sampling, with criteria for companies in various industrial sectors that present complete financial statements in rupiah during 2019 to 2022. So that 30 companies were obtained with 120 observational data during 2019-2022. This research applies analytical techniques in the form of multiple linear regression analysis through normality tests, classical assumption tests, and hypothesis tests. This study used the help of the Statistical Program for Social Science 25 program. The results of this study revealed leverage has a negative effect on financial distress, while liquidity has a positive effect on financial distress